The Use of Code Switching as Teaching Strategy Conducted by EFL Kindergarten Teachers - Sari, Anita (Jurnal Ilmiah Humanika, 2018)
Code switching is commonly used by EFL teachers when teaching English. Nevertheless, the switching is often perceived negatively and sometimes seen as a sign of incompetency in the second language. This study mainly aims at identifying the types of code switching and the use of code switching as teaching strategy conducted by EFL teachers. The data of the research are gathered by the way of classroom observations and interviews. The recording is transcribed and then analyzed to identify the types of code switching. After that, the researcher interviews them to get the data then identify the use of code switching as teachers‘ teaching strategy. In sum, this study indicates that teachers from each level do code switching in their teaching despite they have different strategy while committing code switching in the language classroom.